Banking Mesenchymal Stromal Cells from Umbilical Cord Tissue: Large Sample Size Analysis Reveals Consistency Between Donors. (20th June 2019) - Raileanu, Vanessa N.; Whiteley, Jennifer; Chow, Theresa; Kollara, Alexandra; Mohamed, Aisha; Keating, Armand; Rogers, Ian M.
Abstract: Mesenchymal stromal cells (MSCs) have emerged as candidate cells with therapeutic potential to treat different pathologies. The underlying mechanism is paracrine signaling. The cells secrete proteins that can impact inflammation, apoptosis, angiogenesis, and cell proliferation. All are important in wound healing and tissue regeneration. Although the bone marrow has been the most widely used source of MSCs, umbilical cord tissue (CT) presents a source that is just starting to be used in the clinic, yet can be obtained with more ease and easily stored. Here, we characterize CT-MSCs obtained from multiple donors by analyzing cell surface proteins, differentiation capacity, and proteome profile. Analysis of low, medium, and high passage cells indicates that the morphology and proliferation rate stay constant and with the exception of cluster of differentiation (CD) 105 at late passage, there are no changes in the cell surface protein characteristics, indicating the population does not change with passage. TNF-stimulated gene 6 protein was measured in a subset of samples and variable expression was observed, but this did not impact the ability of the cells to enhance skin regeneration. In conclusion, CT-MSC represents a consistent, easily accessible source of cells for cell therapy. Stem Cells Translational Medicine 2019;8:1041–1054 : Abstract : Bone marrow has been the go-to source of mesenchymal stromal cells, but recently umbilical cord tissue-mesenchymal stromal cells have demonstrated therapeutic efficacy. In this study, we collected and characterized mesenchymal stromal cells from multiple donors for cell surface proteins, differentiation capacity, and proteome profile in order to determine if cord tissue-mesenchymal stromal cells represent a consistent and therapeutic source of cells for regenerative medicine.